2018
DOI: 10.1002/jsp2.1018
|View full text |Cite
|
Sign up to set email alerts
|

Successful fishing for nucleus pulposus progenitor cells of the intervertebral disc across species

Abstract: Background Recently, Tie2/TEK receptor tyrosine kinase (Tie2 or syn. angiopoietin‐1 receptor) positive nucleus pulposus progenitor cells were detected in human, cattle, and mouse. These cells show remarkable multilineage differentiation capacity and direct correlation with intervertebral disc (IVD) degeneration and are therefore an interesting target for regenerative strategies. Nevertheless, there remains controversy over the presence and function of these Tie2 + nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(111 citation statements)
references
References 21 publications
0
110
1
Order By: Relevance
“…As exemplified by the work of Likhitpanichkul et al, which demonstrated that a fibrin‐genipin composition applied as a sealant for a large AF defect in bovine IVD within a bioreactor culture system, could limit the biomechanical deterioration resulting from the defect . The observation period, however, was relatively short and although cell infiltration could be observed, it remains to be determined whether application of cell engraftment is required, especially considering the limited densities and potency of endemic IVD cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As exemplified by the work of Likhitpanichkul et al, which demonstrated that a fibrin‐genipin composition applied as a sealant for a large AF defect in bovine IVD within a bioreactor culture system, could limit the biomechanical deterioration resulting from the defect . The observation period, however, was relatively short and although cell infiltration could be observed, it remains to be determined whether application of cell engraftment is required, especially considering the limited densities and potency of endemic IVD cells …”
Section: Discussionmentioning
confidence: 99%
“…33 The observation period, however, was relatively short and although cell infiltration could be observed, it remains to be determined whether application of cell engraftment is required, especially considering the limited densities and potency of endemic IVD cells. [34][35][36] F I G U R E 3 Gross anatomical change observations. A, Macroscopic observations revealed a decrease in disc height and disappearance of NP structure in group D. Disc height was maintained in group S, and NP structure was similar to that of group C. B, Thompson grading system score was 4.1 at week 4 in group D but gradually degenerated to 4.4 after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…74 Nevertheless, IVD cells are commonly derived from compromised tissue sources presenting low cellular yield and reduced cell potency. 10,74,75 Moreover, standard expansion of NP cells in vitro further reduces their overall potency. 75,76 From our current review, however, neither wnt3a nor wnt5a seem to have a clear beneficial effect on NP cell proliferation induction to enhance cell numbers, maintain overall potency, or induce a chondrogenic phenotype in vitro (Figs.…”
Section: Wnt3a and Wnt5a As Tools For Regeneration Of The Intervertebmentioning
confidence: 99%
“…Primer Sequence. Target Forward primer Reverse primer SOX9 GCACATCAAGACGGAGCAAC AGGTTGAAGGGGCTGTAGGA COL2A1 CCAGGTCCTGCTGGAAAA CCTCTTTCTCCGGCCTTT ACAN GCAGGGATAACGGACTGAAG CAAGAGTAAAGTGGTCATAGTTCAGC COL1A1 CATGTTCAGCTTTGTGGACCT GCAGCTGACTTCAGGGATGT GAPDH CAACTCCCTCAAGATTGTCAGCAA GGCATGGACTGTGGTCATGA serve, and enable cell recovery from their storage condition 12) , which is hindered by rapid dedifferentiation of IVDderived nucleus pulposus (NP) cells in monolayer culture, as indicated by a loss in Aggrecan, type II collagen (COL2A1), and SOX9 expression [13][14][15] , forming an obstacle for the development of NP cell transplantation products 12) . Rho kinase (ROCK) is an intracellular serine/threonineoxidizing kinase that was identified as a target of the Rho protein, a low-molecular-weight GTP-binding protein.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was reported that ROCKi suppresses dedifferentiation during monolayer culture of chondrocytes 16) , the effect of ROCKi on NP cells is less established. As such, it might prove beneficial to examine ROCKi on NP cells to potentially maintain their phenotype for research and therapeutic purposes, in particular considering the need to expand NP cells for obtaining sufficient cell numbers for a therapeutic application 17) , keeping in mind the limited cell yields from IVD specimen 13) . Therefore, we evaluated the impact of ROCKi Y-27632 as a culture medium supplement for maintaining cell phenotype of rat NP cells in monolayer culture for potential translation to prospective cell-based transplantation products.…”
Section: Introductionmentioning
confidence: 99%